Processamento e avaliação da estabilidade de extrato hidrossolúvel a base de castanha-do-Brasil (Bertholletia excelsa) e baru (Dipteryx alata Vogel) - Silva, Kamilla Soares (2017)
To elaborate a better combination of Brazil nut (Bertholletia excelsa) and Baru (Dipteryx alata Vogel) in the development of the mixed water-soluble extract, with good physicochemical, physical and biological stability, a simplex centroid type mixture delineation was performed, a mixture between Brazil nut, Baru almond and water. The Brazil nut and Baru almond water-soluble extract obtained was packed in 220 mL glass bottles and pasteurized in stainless steel casing, then cooled and stored under refrigeration (4 degrees) until the physicochemical, physical, microbiological and sensory determinations. The determinations were performed in triplicate and the results were analyzed by the Statistica software and the mathematical models were generated, tested and validated. In order to obtain a better acceptance of the beverage, in both most accepted extracts in the sensorial analysis a fixed amount of 10,00% (w/v) sugar was added and the amount of preservatives for the reduction of residual taste, reduced. After the definition of the best mixture formulation, determined by global acceptance and purchase intention parameters, the water-soluble extract with the best grade was reprocessed in large scale and stored during 28 days, under 4 degrees refrigeration, evaluating the rheological profile and keeping up with the evolution of physicochemical, microbiological and sensorial analysis parameters. The formulation of water-soluble extract composed by 69.17% (w/w) of water, 9.17% (w/w) of Brazil nut and 21.67% of 10,00% (w/v) sucrose Baru almond was the favorite in the global acceptance test. The mathematical models obtained by the simplex centroid planning achieved better adjustments with the special cubic model proving to be highly predictive. The water-soluble extract presented non-newtonian pseudoplastic fluid behavior. The microbiological determinations did not demonstrate contamination of the beverage over the refrigerated storage time, indicating adequate hygienic handling during the processing and its good biological stability.